The Role of Procreation (Injāb) in Marital Life: A Shift between Classical Islamic Law and Contemporary Fatwas - Rispler-Ḥayyîm, Wardît (Hawwa, 2022)
Classical Islamic marriage and divorce laws focus on both spouses’ ability to perform sexually. In fiqh texts, sexual disability is considered a serious medical condition. The fiqh literature lists certain sexual disabilities unique to men, unique to women, or shared by both sexes. Infertility (ʿuqm) is not found in any of these early fiqh lists, although we have proof in various Islamic religious texts that fertility and procreation have always been highly valued in society. In contemporary fatwas (from the Sunni world), the picture appears reversed, as fertility is given priority over sexual performance. In this paper, I illustrate this shift in attitude between the classical legal texts and contemporary fatwas. Then, I offer possible explanations for it. Among the main motivations suggested for the change are feminist Muslim writings, a growing awareness of human rights in the Islamic world, advanced medical technology, and economic factors.